MENATA PRODUKSI PERIKANAN DAN KELAUTAN RIAU PASCAPEMEKARAN PROVINSI KEPULAUAN RIAU - Aras Mulyadi (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
Legislation of Riau Archipelago Province has influenced the marine and fisheries production of Riau Province. That is why, Riau Province must be importan to arrange marine and fisheries sector to increase its production. Auqaculture production can be developed by 1) Aquaculture based on ecosystem, 2) Aquaculture based on comodities 3) Aquaculture based on product oriented.